2018
DOI: 10.4252/wjsc.v10.i12.196
|View full text |Cite
|
Sign up to set email alerts
|

Functional and molecular mechanism of intracellular pH regulation in human inducible pluripotent stem cells

Abstract: AIMTo establish a functional and molecular model of the intracellular pH (pHi) regulatory mechanism in human induced pluripotent stem cells (hiPSCs).METHODShiPSCs (HPS0077) were kindly provided by Dr. Dai from the Tri-Service General Hospital (IRB No. B-106-09). Changes in the pHi were detected either by microspectrofluorimetry or by a multimode reader with a pH-sensitive fluorescent probe, BCECF, and the fluorescent ratio was calibrated by the high K+/nigericin method. NH4Cl and Na-acetate prepulse techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 66 publications
(97 reference statements)
1
20
0
Order By: Relevance
“…This could be due to the intracellular pH being not the same as the pH value of buffer solutions, especially for the cells in alkaline and acidic environments. As reported in previous studies, the intracellular pH in mammalian cells is maintained within an optimal narrow range through the combined operation of transmembrane transporters and the intracellular buffering capacity [59,60]. The alkaline or acidic buffer solutions changed the intracellular pH, but the intracellular buffering and acid extrusion/loading systems trend to maintain intracellular pH neutral.…”
Section: Cds Ph Response In Living Cellsmentioning
confidence: 59%
“…This could be due to the intracellular pH being not the same as the pH value of buffer solutions, especially for the cells in alkaline and acidic environments. As reported in previous studies, the intracellular pH in mammalian cells is maintained within an optimal narrow range through the combined operation of transmembrane transporters and the intracellular buffering capacity [59,60]. The alkaline or acidic buffer solutions changed the intracellular pH, but the intracellular buffering and acid extrusion/loading systems trend to maintain intracellular pH neutral.…”
Section: Cds Ph Response In Living Cellsmentioning
confidence: 59%
“…Therefore, it is postulated that in PSCs there may also exist a specific pH i regulating mechanism similar to that of cancer cells. Indeed, in our previous study, we found that in hiPSCs the steady-state pH i values were found to be 7.5 ± 0.01 and 7.68 ± 0.01 in HEPES and 5% CO 2 /HCO 3 − -buffered systems, respectively, which were much higher than that in normal adult cells (pH i~7 .2) and similar to that of cancer cells (Chao et al, 2018).…”
Section: And the Acid-loading Transporters Includementioning
confidence: 64%
“…According to our previous study, the expression and activity of acidextruders were decreased during the loss of pluripotency in hiPSCs (Chao et al, 2018). Therefore, we consider that the retaining effect of F I G U R E 4 The acidic environment retained the pluripotency and up-regulate expression of NHE1 in hiPSCs.…”
Section: The Reversed Ph Gradient Upregulated the Acid-extruder Nhe1mentioning
confidence: 85%
See 2 more Smart Citations